Refining UPLC Methodology for Comprehensive Analysis of Molindone and Its Impurities - Balaji Nagarajan; Gunasekar Manoharan; Ganapathy Narayanan Shanmugam; Nataraj Palaniyappan; Abhinav Yarragunta (Recent Developments in Chemistry and Biochemistry Research Vol. 9, 2024)
Background: Sensitive determination of molindone and its impurities to be developed for the molindone drug substance/products. Aim: Effective chromatographic separation was achieved on a phenyl-hexyl stationary phase for the determination of molindone and its related impurities. Methods: The economical and straightforward mobile phase combination delivered in gradient mode at a flow rate of 0.6 mL/min at 254 nm using the phenyl-hexyl column with the dimension of (50 × 2.1 mm, 1.9 µ particles) with the help of an ultra-performance liquid chromatography (UPLC) system. Results: In the developed method, the resolution between molindone and its related compounds was more significant than 2.0. Regression analysis shows an r2 value (correlation coefficient square) greater than 0.999 for molindone and its associated compounds. This method could detect related compounds of molindone at a level below 0.009% with respect to a test concentration of 500 µg/mL for a 2.0 µL injection volume. Conclusion: The method has shown good, consistent recoveries for related compounds (90-110%). The test solution was found to be stable in the diluent for 48 hours. The drug was subjected to stress conditions. The mass balance was found to be close to 99.3%. The validated method may be used for the routine analysis of the determination of related compounds of molindone from the bulk drug, pharmaceutical preparation, and other quality control samples of product development.